The Mindfulness Levels of Adults During the Covid-19 Pandemic: The Role of Solution Focused Thinking and Valuing - Faika Şanal Karahan; Orkide Bakalım (Spiritual Psychology and Counseling)
The aim of this research is to identify the role of solution focused thinking and valuing on mindfulness among adults during the Covid-19 pandemic. The data were obtained through convenience sampling via an online platform. Accordingly, a total of 669 people, 357 men and 314 women, were reached. Personal information form, Mindful Attention Awareness Scale, Solution Focused Inventory and Valuing Questionnaire were used to collect the data. Stepwise regression analysis was conducted to test whether progress, obstruction, goal achievement, problem disengagement and resource activation were meaninful predictors of mindfulness. When the research findings were examined in detail, it was determined that the obstruction variable was the strongest predictor of mindfulness in adults in the Covid-19 period. Other significant predictors, respectively, were determined to be problem disengagement, resource activation and progress. On the other hand, it was determined that goal orientation is not a significant predictor of mindfulness. The research findings were discussed within the scope of the literature and recommendations were made.